LRFD guide specifications for the design of pedestrian bridges. (American Association of State Highway and Transportation Officials, 2009)
"These Guide Specifications address the design and construction of typical pedestrian bridges which are designed for, and intended to carry, primarily pedestrians, bicyclists, equestrian riders and light maintenance vehicles, but not designed and intended to carry typical highway traffic. Pedestrian bridges with cable supports or atypical structural systems are not specifically addressed. These Guide Specifications provide additional guidance on the design and construction of pedestrian bridges in supplement to that available in the AASHTO LRFD Bridge Design Specifications (AASHTO LRFD). Only those issues requiring additional or different treatment due to the nature of pedestrian bridges and their loadings are addressed. In Article 3 of this document, the load definitions and abbreviations are taken from AASHTO LRFD. Aluminum and wood structures are adequately covered in AASHTO LRFD, and as such are not specifically addressed herein. Implementation of the wind loading and fatigue loading provisions require reference to the AASHTO Standard Specifications for Structural Supports for Highway Signs, Luminaries and Traffic Signals (AASHTO Signs)."--Page 1.